Highly flexible resistive switching memory based on amorphous-nanocrystalline hafnium oxide films. Issue 21 (2nd March 2017) - Shang, Jie; Xue, Wuhong; Ji, Zhenghui; Liu, Gang; Niu, Xuhong; Yi, Xiaohui; Pan, Liang; Zhan, Qingfeng; Xu, Xiao-Hong; Li, Run-Wei
Abstract : A highly flexible ITO/HfO x /ITO/PET structured memory device was fabricated by optimizing the microstructure of the HfOx switching layer, which not only shows good mechanical performance but also reliable resistive switching behaviors for wearable applications. Abstract : Flexible and transparent resistive switching memories are highly desired for the construction of portable and even wearable electronics. Upon optimization of the microstructure wherein an amorphous-nanocrystalline hafnium oxide thin film is fabricated, an all-oxide based transparent RRAM device with stable resistive switching behavior that can withstand a mechanical tensile stress of up to 2.12% is obtained. It is demonstrated that the superior electrical, thermal and mechanical performance of the ITO/HfO x /ITO device can be ascribed to the formation of pseudo-straight metallic hafnium conductive filaments in the switching layer, and is only limited by the choice of electrode materials. When the ITO bottom electrode is replaced with platinum metal, the mechanical failure threshold of the device can be further extended.